Changes in serum thiol-disulphide homeostasis in sheep with gastrointestinal nematodes - Schmidt, Elizabeth Moreira dos Santos [UNESP] (2021)
This work aimed to evaluate the thiol-disulphide homeostasis in serum of lambs naturally infected by gastrointestinal nematodes presenting different levels of parasite load indirectly indicated by faecal worm egg counts (EPG). Furthermore, the possible changes in the thiol-disulphide dynamic after different procedures to reduce the parasitic charge, such as the integrated crop-livestock system or anthelmintic treatment, were assessed. The results were compared with a panel of various oxidative stress and inflammatory biomarkers. The lambs were divided into three groups: animals highly infected (EPG higher than 5000) and packed cell volume (PCV) lower than 24% (G1); animals highly infected (EPG higher than 5000) and normal PCV (>24%) (G2); and animals presenting EPG lower than 5000 and normal PCV (>24%) (G3). The highly infected lambs (G1 and G2) showed lower total thiol (TT) and native thiol (SH) (p ≤ 0.01) than those from G3. After treatment, TT and SH increased significantly in all groups (p ≤ 0.01), and the disulphide (SS)/TT and SS/SH ratios decreased significantly (p < 0.01) in G1 and G2. These results show that the thiol-disulphide balance was impaired in lambs infected by gastrointestinal nematodes and that it could be potentially used as a biomarker to monitor this disease.